Sociodemographic Factors Associated with Social Tolerance for Intimate Partner Violence in Peru: Evidence from the National Survey of Social Relations, 2019 - Caira-Chuquineyra, Brenda (Journal of interpersonal violence, 2023)
Our objective was to determine the factors associated with social tolerance for intimate partner violence (IPV) in the Peruvian population. A population-based cross-sectional study was conducted. Data from the 2019 National Survey of Social Relations (ENARES) of Peru were used. This survey collected data from a total of 1,026 Peruvians aged 18 years and older. Multilevel linear regression models were performed to evaluate the factors associated with a standardized index of social tolerance for IPV. Likewise, a stratified analysis was performed according to sex. Being older (β = .01; 95% confidence interval [CI]: .01–.01) and living outside the capital (β = 0.24; 95% CI: .07–0.41) were associated with greater social tolerance for IPV. On the other hand, being female (β = −0.26; 95% CI: −0.36 to −0.17) and having a higher educational level were associated with lower tolerance. In the stratified analysis by sex, in both men and women, being older and having a higher level of education were associated with higher and lower tolerance for IPV, respectively. On the other hand, living outside the capital was associated with greater tolerance only in men. In Peru, older people and those living outside the capital showed greater acceptance of IPV, while women and those with higher levels of education expressed rejection of IPV.